2013
DOI: 10.7755/fb.111.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Establishing species–habitat associations for 4 eteline snappers with the use of a baited stereo-video camera system

Abstract: Abstract-With the use of a baited stereo-video camera system, this study semiquantitatively defined the habitat associations of 4 species of Lutjanidae: Opakapaka (Pristipomoides filamentosus), Kalekale (P. sieboldii), Onaga (Etelis coruscans), and Ehu (E. carbunculus). Fish abundance and length data from 6 locations in the main Hawaiian Islands were evaluated for speciesspecific and size-specific differences between regions and habitat types. Multibeam bathymetry and backscatter were used to classify habitats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 14 publications
3
34
0
Order By: Relevance
“…Previous studies on habitat association of the Deep-7 bottomfish species in the MHI region also showed that depth and slope were important predictors of encounter probability (Misa et al 2013, Oyafuso et al 2017. For example, Oyafuso et al (2017) showed that apart from depth, ridge-like features, backscatter, and rugosity at a 5 or 60 m resolution explained most of the deviance in species-specific models.…”
Section: Importance Of Bathymetry Geomorphology and Spatial Resolutmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies on habitat association of the Deep-7 bottomfish species in the MHI region also showed that depth and slope were important predictors of encounter probability (Misa et al 2013, Oyafuso et al 2017. For example, Oyafuso et al (2017) showed that apart from depth, ridge-like features, backscatter, and rugosity at a 5 or 60 m resolution explained most of the deviance in species-specific models.…”
Section: Importance Of Bathymetry Geomorphology and Spatial Resolutmentioning
confidence: 86%
“…For example, Maui Nui and the deep channel between Maui and Hawai'i, the 'Au'au Channel, are known hotspots for the deepwater coral species Leptoseris spp. (Kahng & Kelley 2007 and Penguin Bank for various species of deepwater snappers (Misa et al 2013).…”
Section: Penguin Bank and Maui Nui Are Hotspots Of Fish Biomassmentioning
confidence: 99%
“…In particular, the appearance of larger groupers and snappers during the 2016 El Niño year produced a distinct catch composition. Grouper and snapper species can exhibit size-depth distribution (Aburto-Oropeza et al, 2009;Misa et al, 2013;Lindfield, McIlwain & Harvey, 2014), suggesting fishers may have been catching larger fish because these were moving to shallower waters where production can be higher than in deeper waters in the Galapagos even during El Nino events (Wolff, Ruiz & Taylor, 2012). However, very little evidence of such size-depth partitioning has been reported in Galapagos for adult Groupers such as M. olfax (Coello & Grimm, 1993;Nicolaides et al, 2002), or snappers such as L. argentiventris (Aguaiza, 2015;Fierro Arcos, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical and modelled applications in this field seem to be well established (e.g. Johnson 1980, Aarts et al 2008, 2013, but both field and laboratory Laurel et al 2007, Misa et al 2013). This interchangeable use of terms may arise from the overlapping definitions of association, selection and preference (e.g.…”
Section: Concepts and Definitionsmentioning
confidence: 99%
“…This has typically been measured by comparing relative abundances or densities of individuals in, on, or over different substratum types (e.g. Nickell & Sayer 1998, Misa et al 2013. Here, substratum association refers to all the substrata that the fish occupies during a particular stage in its life cycle without any consideration as to whether an active choice was made to reside in the given substrata.…”
Section: Krausman 1999 and Morris 2003) To Support Implementation Ofmentioning
confidence: 99%